A glycopyrronium bromide 1% cream for topical treatment of primary axillary hyperhidrosis: efficacy and safety results from a phase IIIa randomized controlled trial. (1st August 2021) - Abels, C.; Soeberdt, M.; Kilic, A.; Reich, H.; Knie, U.; Jourdan, C.; Schramm, K.; Heimstaedt‐Muskett, S.; Masur, C.; Szeimies, R.‐M.
Summary: Background: Effective topical treatment options for patients with primary axillary hyperhidrosis (PAHH) are limited. A phase I trial showed promising results regarding the efficacy and safety of a topical cream containing glycopyrronium bromide (GPB). Objectives: To assess the efficacy, safety and tolerability of a 4‐week topical treatment of GPB 1% cream in patients with PAHH vs. placebo. Methods: In total, 171 patients (84 receiving placebo; 87 receiving GPB 1%) with PAHH were included in the 4‐week, multicentre, randomized, double‐blind, placebo‐controlled phase IIIa part of the pivotal study. Sweat production was measured by gravimetry. Patients rated the impact of disease with the Hyperhidrosis Disease Severity Scale (HDSS) and Hyperhidrosis Quality of Life Index (HidroQoL © ). Results: Absolute change in sweat production from baseline to day 29 in logarithmic values was significantly larger in the GPB 1% group compared with the placebo group ( P = 0·004). The improvement in HidroQoL exceeded the minimal clinically important difference of 4. The proportion of responders was twofold higher for sweat reduction (–197·08 mg GPB 1% vs. –83·49 mg placebo), HDSS (23% GPB 1% vs. 12% placebo) and HidroQoL (60% GPB 1% vs. 26% placebo). Treatment was safe: most treatment‐emergent adverse effects were mild or moderate, and transient. Local tolerability was very good, with 9% of patients having only mild or moderate application‐site reactions. The most reported adverse drug reaction was dry mouth (16%), an expected anticholinergic effect of the treatment. Conclusions: GPB 1% cream may provide an effective new treatment option exhibiting a good safety profile for patients with PAHH. The long‐term open‐label part (phase IIIb) is ongoing.